2013
DOI: 10.4236/jct.2013.46124
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of Some Trace Element and Heavy Metals in Patients with Metastatic Colon Cancer

Abstract: Purpose: It is well known that trace elements and heavy metals play a significant role in human health and disease. These elements play an important role in different metabolic pathways of cells and tissues. Trace element deficiency or excess is implicated in the development or progression of some cancers. We present a study which investigates serum/ plasma levels of trace-heavy elements in metastatic colon cancer patients and healthy subjects. Methods: Blood samples were collected from 29 healthy subjects and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…It was presented by a study in Turkey that Pb level in renal cell carcinoma increased significantly compared to healthy people [16]. A literature on colon cancer found out that Pb level was higher than those of healthy people [10]. In this study, Pb level in ovarian cancer patients was found higher in the preoperative group compared to control group but lower than those of postoperative group and statistically significant.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…It was presented by a study in Turkey that Pb level in renal cell carcinoma increased significantly compared to healthy people [16]. A literature on colon cancer found out that Pb level was higher than those of healthy people [10]. In this study, Pb level in ovarian cancer patients was found higher in the preoperative group compared to control group but lower than those of postoperative group and statistically significant.…”
Section: Discussionmentioning
confidence: 54%
“…The fact that Zn and Cu levels were found low in the same patient group was associated to low enzyme activity. In a study on colon cancer in the literature, Zn level was found higher compared to those of healthy people [10]. A research discovered that Zn level in lung cancer patients was significantly lower than those of healthy control group [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations